2001
DOI: 10.1038/nn783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of the t-SNARE SNAP-25 distinguishes mechanisms of neuroexocytosis

Abstract: Axon outgrowth during development and neurotransmitter release depends on exocytotic mechanisms, although what protein machinery is common to or differentiates these processes remains unclear. Here we show that the neural t-SNARE (target-membrane-associated-soluble N-ethylmaleimide fusion protein attachment protein (SNAP) receptor) SNAP-25 is not required for nerve growth or stimulus-independent neurotransmitter release, but is essential for evoked synaptic transmission at neuromuscular junctions and central s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
500
5
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(546 citation statements)
references
References 47 publications
35
500
5
6
Order By: Relevance
“…We recorded miniature excitatory (mEPSCs) or inhibitory (mIPSCs) currents (Fig 1A-B), holding neurons at the reversal potential for GABA (g-aminobutyric acid)-and glutamate-mediated responses (-70 and þ 5 mV, respectively) in the presence of 1 mM tetrodotoxin. Frequency and amplitudes of both mEPSCs and mIPSCs were not significantly different in het neurons relative to wt, in line with previous reports [19,3,18] Fig 1C,E). Conversely, a slight, although significant, reduction of evoked IPSC amplitude was recorded in het neurons relative to wt (0.52±0.03 versus 0.36±0.03 nA, wt versus het, Po0.05; Fig 1D,E).…”
Section: Results and Discussion Glutamatergic Currents In Developing supporting
confidence: 93%
“…We recorded miniature excitatory (mEPSCs) or inhibitory (mIPSCs) currents (Fig 1A-B), holding neurons at the reversal potential for GABA (g-aminobutyric acid)-and glutamate-mediated responses (-70 and þ 5 mV, respectively) in the presence of 1 mM tetrodotoxin. Frequency and amplitudes of both mEPSCs and mIPSCs were not significantly different in het neurons relative to wt, in line with previous reports [19,3,18] Fig 1C,E). Conversely, a slight, although significant, reduction of evoked IPSC amplitude was recorded in het neurons relative to wt (0.52±0.03 versus 0.36±0.03 nA, wt versus het, Po0.05; Fig 1D,E).…”
Section: Results and Discussion Glutamatergic Currents In Developing supporting
confidence: 93%
“…*Po0.05; **Po0.01; ***Po0.001 release is not required for excitatory synapse formation, 52,53 the number of synapses formed in the absence of neurotransmitter release is dramatically decreased, 54 suggesting that glutamate release could influence excitatory synaptogenesis. 55 Given that SNAP-25 has a critical role at the presynaptic terminal during synaptic vesicle fusion and considering the possible role of presynaptic function in the maturation of the postsynaptic compartment, the postsynaptic effects observed here might have been the result of SNAP-25-related alterations in presynaptic release, 7 even if electron microscopy studies showed that reduced levels of SNAP-25 do not alter the presynaptic terminal structure and vesicles content. 56 By taking advantage of mixed cultures of wt and Het neurons, we demonstrated that postsynaptic defects in In recent years SNARE/SM proteins have been shown to be involved in activity-dependent AMPA receptor exocytosis during LTP 22 and SNAP-25, in particular, has been reported to have a role in the removal of kainate receptors from the postsynaptic membrane, 57 in the insertion of NMDA receptors in neuronal plasma membrane 21 and of P/Q and L typevoltage gated calcium channels.…”
Section: Discussionmentioning
confidence: 88%
“…5,6 A hallmark of synaptic specializations is their dependence on highly organized complexes of proteins that interact with each other. Therefore, the loss or modification of key synaptic proteins might directly affect the properties of such networks and, ultimately, synaptic function.SNAP-25 is a component of the SNARE complex, which is central to synaptic vesicle exocytosis 7,8 and which has a role in the regulation of voltage-gated calcium channels. 9,10 The SNAP25 gene has been associated with attention deficit hyperactivity disorder (ADHD) 11,12 and with schizophrenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the significant increase in SNAP25 protein level previously reported in Brodmann's area 9 (dorsolateral prefrontal cortex) in patients with BD, 15 as cellular and animal studies showed that variations in mRNA levels of SNAP25 correspond to equivalent variation in protein levels. 32,33 The SNP4 is located between two AP-1 consensusbinding sequences in a region that contributes to the repression of the SNAP25 transcription by binding of POU4F2 (also called Brn-3b). 30,34 This protein is a member of the Pict-Oct-Unc (POU) transcription factor family that involved in the development of the mammalian nervous system and for which an overexpression results in a failure of SNAP25 activation and neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%